Mextli Is a Novel Eukaryotic Translation Initiation Factor 4E-Binding Protein That Promotes Translation in Drosophila melanogaster. - Hernández, G.; Miron, M.; Han, H.; Liu, N.; Magescas, J.; Tettweiler, G.; Frank, F.; Siddiqui, N.; Sonenberg, N.; Lasko, P. (Molecular and Cellular Biology, 2013)
Translation is a fundamental step in gene expression, and translational control is exerted in many developmental processes. Most eukaryotic mRNAs are translated by a cap-dependent mechanism, which requires recognition of the 5'-cap structure of the mRNA by eukaryotic translation initiation factor 4E (eIF4E). eIF4E activity is controlled by eIF4E-binding proteins (4E-BPs), which by competing with eIF4G for eIF4E binding act as translational repressors. Here, we report the discovery of Mextli (Mxt), a novel Drosophila melanogaster 4E-BP that in sharp contrast to other 4E-BPs, has a modular structure, binds RNA, eIF3, and several eIF4Es, and promotes translation. Mxt is expressed at high levels in ovarian germ line stem cells (GSCs) and early-stage cystocytes, as is eIF4E-1, and we demonstrate the two proteins interact in these cells. Phenotypic analysis of mxt mutants indicates a role for Mxt in germ line stem cell (GSC) maintenance and in early embryogenesis. Our results support the idea that Mxt, like eIF4G, coordinates the assembly of translation initiation complexes, rendering Mxt the first example of evolutionary convergence of eIF4G function.